Histone deacetylase 6 and cytoplasmic linker protein 170 function together to regulate the motility of pancreatic cancer cells. Issue 3 (29th January 2014) - Li, Dengwen; Sun, Xiaodong; Zhang, Linlin; Yan, Bing; Xie, Songbo; Liu, Ruming; Liu, Min; Zhou, Jun
Abstract: Pancreatic cancer is a devastating disease with the worst prognosis among all the major human malignancies. The propensity to rapidly metastasize contributes significantly to the highly aggressive feature of pancreatic cancer. The molecular mechanisms underlying this remain elusive, and proteins involved in the control of pancreatic cancer cell motility are not fully characterized. In this study, we find that histone deacetylase 6 (HDAC6), a member of the class II HDAC family, is highly expressed at both protein and mRNA levels in human pancreatic cancer tissues. HDAC6 does not obviously affect pancreatic cancer cell proliferation or cell cycle progression. Instead, it significantly promotes the motility of pancreatic cancer cells. Further studies reveal that HDAC6 interacts with cytoplasmic linker protein 170 (CLIP-170) and that these two proteins function together to stimulate the migration of pancreatic cancer cells. These findings provide mechanistic insight into the progression of pancreatic cancer and suggest HDAC6 as a potential target for the management of this malignancy.